La construction symbolique du territoire - Séverine Steenhuyse (Projets de Paysage)
The site of the Pond of Berre (l’étang-de-Berre, Bouches-du-Rhônes) has been radically transformed by the industrial and commercial development of the 1960s and the 1970s. Its landscape, which was formerly considered as picturesque, has vanished and is now missing from the collective representations. Which method could be implemented, in order to have access to a subtle understanding of the symbolical phenomenon that occurred ? And, upon which values can the building of a popular collective landscape be carried out ? In order to develop some leads in that sense, the suggested method relied on the enhancing of the inhabitants’ word.